Systematic Overview on Nanosponges - Ahire, Umesh R.; Dr Prashant S. Malpure; Talele, Dr Gokul S.; Kolpe, Snehal S. (Asian Journal of Pharmaceutical Research and Development, 2024)
Nano sponges are the most recent advancements in nanotechnology. The original goal of nanosponge delivery technology was to deliver topical medications. Water soluble and bioerodible polymers can now be used to administer medications orally. Nano sponges are permeable structures with a diameter of less than 1m, comparable to viruses in size. Because of their small size and porous nature, nanosponges can bind to poorly soluble medicines and increase their bioavailability. These nanosponges can bind to specific target sites and travel throughout the body. Begin the controlled release of the drug at the intended site. For the fabrication of nanosponges, numerous methods have been reported, including the melt method, solvent diffusion method, solvent method, ultrasound assisted approach, and sonication. Nanosponges for targeted medication delivery. A particular kind of nanoparticle is a nanosponge, which is often a synthetic polymer containing carbon. Because of its porous nature, which has pores ranging in size from 1-2 nanometers, they can be used to absorb trace amounts of material or toxins. In medicine, nanosponges are frequently employed as targeted drug delivery vehicles, detoxifying techniques, or post-injury damage management measures. They can also be employed in environmental applications, such as water purification or metal deposit removal, to improve ecosystems. Because of their microscopic size, they can move swiftly through liquids like blood or water, effectively locating and eliminating undesirable material. In order to increase their effectiveness when injected into the body, natural elements are frequently added to synthetically made nanosponges. The best are nanosponges. The prefix Nano implies that items of this size are measured on a scale of meters.